Pengaruh Profitabilitas dan Ukuran Perusahaan Pada Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Pemoderasi - Wasista, I Putu Putra; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2019)
Profitability and company size are two of the many factors that influence a company's value. Implementation of Good Corporate Governance (GCG) is very important so that it can affect the relationship between profitability and company size on firm value. This research was conducted on 31 manufacturing companies with a 5-year observation period, namely 2013 to 2017, then the total sample of observations was 155 samples. Obtained 155 observational samples through the purposive sampling method. MRA or Moderated Regression Analysis is a data analysis technique used in this study. The results of data analysis obtained are that there is a positive influence between the relationship of profitability and firm size on firm value and found that GCG is a moderating variable that reinforces the effect of profitability and firm size on firm value. Keywords : Profitability; Company Size; Good Corporate Governance; The Value of The Company.